Emergence of norovirus GII.2 and its novel recombination during the gastroenteritis outbreak in Japanese children in mid-2016 - Thongprachum A. (2017)
© 2017 Elsevier B.V. In mid-2016, norovirus GII.2 emerged as a major cause of gastroenteritis outbreak in Japan with overall detection rate of 56.3% of norovirus cases. The differences in ORF1 and ORF2 of some norovirus GII were observed. Inter-subtype recombinants GII.Pe/GII.2, GII.P16/GII.2 and GII.P17/GII.2 were detected. Three amino acid substitutions were noted at P2 antigenic site of GII.P16/GII.2 recombinants. Furthermore, this study revealed that the current immunochromatographic kit available in Japan could be used effectively for the detection of recent GII.2 genotype.